Impact of Trametes versicolor and Phanerochaete chrysosporium on differential breakdown of pesticide mixtures in soil microcosms at two water potentials and associated respiration and enzyme activity. - Fragoeiro, Silvia; Magan, Naresh (Elsevier, 2008)
This study has examined the effect of inoculation of soil microcosms with Trametes versicolor and Phanerochaete chrysosporium on wood chips on differential degradation of pesticides (simazine, trifluralin and dieldrin, 10 mg kg−1 soil) at two water potentials (−0.7 and −2.8 MPa) at 15 °C. The soil microcosms were destructively sampled after 6/12 weeks and four extracellular enzymes quantified, respiration and pesticides measured with GC and HPLC. The fungal treatments produced extracellular enzymes in soil. Respiratory activity was significantly (P = 0.05) enhanced in soil with the inocula, and higher in the pesticide mixtures. Cellulase/dehydrogenase increased in inoculated soil. Laccase increased significantly in the T. versicolor treatment. Degradation of the three pesticides by wood chip addition alone was enhanced (20–30%). T. versicolor increased degradation of simazine (27–46%), trifluralin (5–17%) and dieldrin (5–11%) and P. chrysosporium by 34–48%, 0–30% and 40–46%, respectively, when compared with controls after 12 weeks. This study has demonstrated that pesticide mixtures are differentially degraded by fungal inoculants and significant extracellular enzymes are produced in soil, even at −2.8 MPa water potential. This suggests that effective bioremediation of xenobiotic mixtures using wood chips and fungal inoculants is achievable over a relatively wide water potential range when compared with that allowing plant growth (−1.4 MPa).
Keywords: Trametes versicolor; Phanerochaete chrysosporium; Bioremediation; Pesticides; Water potential; Hydrolytic enzymes; Soil microcosms